Acute and Chronic Effects of Rifampin on Letermovir Suggest Transporter Inhibition and Induction Contribute to Letermovir Pharmacokinetics. Issue 3 (15th January 2022) - Robbins, Jonathan A.; Menzel, Karsten; Lassman, Michael; Zhao, Tian; Fancourt, Craig; Chu, Xiaoyan; Mostoller, Kate; Witter, Rose; Marceau West, Rachel; Stoch, S. Aubrey; McCrea, Jacqueline B.; Iwamoto, Marian
Abstract : Rifampin has acute inhibitory and chronic inductive effects that can cause complex drug–drug interactions. Rifampin inhibits transporters including organic‐anion‐transporting polypeptide (OATP)1B and P‐glycoprotein (P‐gp), and induces enzymes and transporters including cytochrome P450 3A, UDP‐glucuronosyltransferase (UGT)1A, and P‐gp. This study aimed to separate inhibitory and inductive effects of rifampin on letermovir disposition and elimination (indicated for cytomegalovirus prophylaxis in hematopoietic stem cell transplant recipients). Letermovir is a substrate of UGT1A1/3, P‐gp, and OATP1B, with its clearance primarily mediated by OATP1B. Letermovir (single‐dose) administered with rifampin (single‐dose) resulted in increased letermovir exposure through transporter inhibition. Chronic coadministration with rifampin (inhibition plus potential OATP1B induction) resulted in modestly decreased letermovir exposure vs. letermovir alone. Letermovir administered 24 hours after the last rifampin dose (potential OATP1B induction) resulted in markedly decreased letermovir exposure. These data suggest rifampin may induce transporters that clear letermovir; the modestly reduced letermovir exposure with chronic rifampin coadministration likely reflects the net effect of inhibition and induction. OATP1B endogenous biomarkers coproporphyrin (CP) I and glycochenodeoxycholic acid‐sulfate (GCDCA‐S) were also analyzed; their exposures increased after single‐dose rifampin plus letermovir, consistent with OATP1B inhibition and prior reports of inhibition by rifampin alone. CP I and GCDCA‐S exposures were substantially reduced with letermovir administered 24 hours after the last dose of rifampin vs. letermovir plus chronic rifampin coadministration. This study suggests that OATP1B induction may contribute to reduced letermovir exposure after chronic rifampin administration, although given the complexity of letermovir disposition alternative mechanisms are not fully excluded.